PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SENI BUDAYA SUB. BIDANG STUDI SENI RUPA PESERTA DIDIK KELAS VII SMP NEGERI 1 LUBUK ALUNG - ELSA FITRI, Dr. Ramalis Hakin, M.Pd., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2017)
Research involved in learning can pursue various things to improve optimal learning outcomes. In the learning process a teacher is expected to be able to use an interesting learning model that can stimulate students to learn actively. Title of research: Influence of Using Learning Model Contectual Teaching and Learning To The Learning Result Of Art Culture Sub Division Of Fine Arts Study At Grade VII Student SMPN 1 Lubuk Alung. The research used quantitative approach with quasi experimental method, the sample in this research is class VII.1 control class 30 students, class VII.2 experimental class 29 people. Sample technique used in this study random sampling.Berdasarkan hypothesis test results obtained ttable 1.699 and tcount of 3.579. It can be concluded that there are differences in student learning outcomes are significant between the given learning model of CTL by using the conventional model and tcount 3.579> ttabel 1.699. Researchers suggest for learners, especially school subject teachers to try to use the CTL model in the learning process.Kata kunci: CTL learning model and learning outcomes.